Quality measurement for rhinosinusitis: a review from the Quality Improvement Committee of the American Rhinologic Society. Issue 9 (30th June 2017) - Rudmik, Luke; Mattos, Jose; Schneider, John; Manes, Peter R.; Stokken, Janalee K.; Lee, Jivianne; Higgins, Thomas S.; Schlosser, Rodney J.; Reh, Douglas D.; Setzen, Michael; Soler, Zachary M.
Abstract : Background: Measuring quality outcomes is an important prerequisite to improve quality of care. Rhinosinusitis represents a high value target to improve quality of care because it has a high prevalence of disease, large economic burden, and large practice variation. In this study we review the current state of quality measurement for management of both acute (ARS) and chronic rhinosinusitis (CRS). Methods: The major national quality metric repositories and clearinghouses were queried. Additional searches included the American Academy of Otolaryngology–Head and Neck Surgery database, PubMed, and Google to attempt to capture any additional quality metrics. Results: Seven quality metrics for ARS and 4 quality metrics for CRS were identified. ARS metrics focused on appropriateness of diagnosis (n = 1), antibiotic prescribing (n = 4), and radiologic imaging (n = 2). CRS quality metrics focused on appropriateness of diagnosis (n = 1), radiologic imaging (n = 1), and measurement of patient quality of life (n = 2). The Physician Quality Reporting System (PQRS) currently tracks 3 ARS quality metrics and 1 CRS quality metric. There are no outcome‐based rhinosinusitis quality metrics and no metrics that assess domains of safety, patient‐centeredness, and timeliness of care. Conclusions: The current status of quality measurement for rhinosinusitis has focused primarily on the quality domain of efficiency and process measures for ARS. More work is needed to develop, validate, and track outcome‐based quality metrics along with CRS‐specific metrics. Although there has been excellent work done to improve quality measurement for rhinosinusitis, there remain major gaps and challenges that need to be considered during the development of future metrics.